Contraceptive use and discontinuation among women aged 15–24 years in Kenya - Kungu, Wambui (Frontiers in Reproductive Health, 2023)
The 15-24-year-old age group of young women make up about 15% of the population of 47 million Kenyans which comes to 7 million. Addressing the reproductive health goals of this cohort is thus a policy priority because of the high potential they pose for unintended pregnancy through incorrect and intermittent use of contraception.The study sought to present evidence on contraceptive use among women aged 15-24 in Kenya between 2012 and 2014 using Kenya Demographic and Health Survey (KDHS) 2014 Contraceptive calendar data and make recommendations on enhancing the correct and consistent use of contraception.The data used was obtained from the Choices and Challenges tool developed by Population Reference Bureau (PRB) and visualized innovatively using Sankey Diagrams that show contraceptive use/non-use, continuation, switching/discontinuation, and pregnancy.The use of contraceptives went up by about 30% during the study period while the use of modern methods went up by 83%. The uptake of Long-Acting Reversible Contraception (LARC) went up by 87% while that of Short Acting Methods (SAM) went up by 70% but the progress was clouded by discontinuation rates of 35% with side effects being the leading reason for the abandonment of contraception.For Kenya to achieve transformative results in ending the unmet need for contraception and preventable maternal deaths, it is critical to sustaining the current gains in contraceptive prevalence rate (CPR) by promoting the retention of youth users and encouraging new users.